밀도층 유체에서 해양 방사파 패턴 특징 - 민은홍(Eun-Hong Min); 최하윤(Ha-Yun Choi); 김영규(Young-Gyu Kim); 백광준(Kwang-Jun Paik); 구원철(Weon-Cheol Koo) (Han-guk haeyang gonghak hoeji (Online), 2019)
The sea is stratified with water that has different densities because of pressure, temperature, and salinity. When conducting studies of internal waves in the ocean, the fluid is assumed to have layers that have discrete densities. This assumption is made because it is difficult to achieve layers that exhibit gradual changes in the density of the water. In this study, we used previous studies on ocean waves and their radiation issues in the density layer fluid to investigate the characteristics of internal waves in the ocean and their radiation patterns induced by a moving body in a stratified fluid. We also studied the difference in wave radiation between the density gradient layer and the discrete density layer. We found that the wave radiation patterns depended on the velocity of the moving body and the change in the density of the water. The crest apex shift phenomenon was observed in the density gradient in the layer of fluid.